(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Polycystic ovarian syndrome (PCOS) is one of the most prevalent endocrine diseases in reproductive women and occurs in conjunction with the systemic hormonal derangement and metabolic disease processes associated with the disease. The steroid hormone sex hormones have a major impact on the physiology of the ocular surface (OS), the function of the lacrimal gland (LG), the activity of the meibomian glands (MG), and the stability of the tear film (TF). Dry eye disease (DED) and OS abnormalities are becoming more prevalent in the PCOS population. Schirmer’s test (ST) and Tear Film Break Up Time (TBUT) are the conventional means to evaluate dry eye disease. Conjunctival impression cytology (CIC) is a test that might assess the earliest cytologic changes associated with dry eye prior to demonstrating clinical evidence of dry eye through the surface abnormality of the tear film. There has been little evidence comparing conjunctival impression cytology to traditional assessments of dry eye disease using Scheimer’s test and TBUT in patients newly diagnosed with PCOS. Aim: To comparatively evaluate conjunctival impression cytology and tear film tests in early diagnosis of dry eye among newly diagnosed patients with polycystic ovarian syndrome. Objectives • To evaluate Schirmer’s Test 1 and Tear Film Breakup Time findings in newly diagnosed PCOS patients. • To assess conjunctival impression cytology changes in newly diagnosed PCOS patients. • To determine the correlation between conjunctival impression cytology grading and tear film test findings. • To evaluate whether conjunctival impression cytology detects ocular surface abnormalities earlier than routine clinical tear film tests. Methodology: The research employed as a design a cross sectional observation study with data collected from patients visiting a tertiary care hospital Department of Ophthalmology as well as Obstetrics and Gynecology. Patients with PCOS who fit the criteria above were selected based upon their age range of 18-45 years. The patients who satisfied the criteria for a diagnosis of PCOS were evaluated based upon the 2003 Rotterdam Criteria (RC), and each underwent a Schirmer’s Test 1, Tear Breakup Assessment, and a conjunctival impression cytology from their right eye. The conjunctival impression cytology specimens were graded according to Nelson’s grading system. The Statistical analysis used to assess the association between the CIC Grading and Tear Tests was carried out with the use of statistical software SPSS, and the relationship between the CIC Grading and Tear Tests was assessed using Pearson or Spearman correlation coefficients. Results: Most of the participants in the study were aged 21-25. A total of 38.7% of subjects had abnormal results on the Schirmer’s test, 44% had abnormal (TBUT) results and 68% of subjects demonstrated conjunctival impression cytology abnormalities. The conjunctival impression cytology demonstrated higher positivity rates compared to the Schirmer’s test or TBUT. Grade 1 conjunctival impression cytology abnormalities accounted for the majority of abnormal results in the study. There were decreasing amounts of Schirmer’s test results and TBUT results as the conjunctival impression cytology grades increased. The correlation between conjunctival impression cytology grade and Schirmer’s test result was negative and statistically significant (r = -0.68, p <0.001); likewise, the correlation between conjunctival impression cytology grade and TBUT result was negative and statistically significant (r = -0.74, p <0.001). Most importantly, many patients whose results were clinically normal for both Schirmer’s test and TBUT had an abnormal conjunctival impression cytology, indicating that preclinical ocular surface changes may occur prior to the results of the routine clinical tests. Conclusion: Cytology of the conjunctival surface has proven to be an accurate, non-invasive way of diagnosing patients with polycystic ovarian syndrome (PCOS) who are experiencing alterations to their ocular surface at an early stage. The detection of cytological changes is dependent upon routine testing of the patient’s tears using traditional methods like Schirmer’s test and TBUT; however, it has been found that cytological changes can occur prior to any observable changes occurring to the patient’s tear film. By incorporating these diagnostic tools into a complete ocular evaluation for patients who are newly diagnosed with PCOS, ophthalmologists will have a greater opportunity for diagnosing patients with subclinical dry eye syndrome, and consequently, to provide a timely intervention to help prevent any further deterioration of their ocular health.